Antimicrobial synergism and antibiofilm activity of amoxicillin loaded citric acid-magnesium ferrite nanocomposite: Effect of UV-illumination, and membrane leakage reaction mechanism. (March 2022) - El-Batal, Ahmed I.; Al-Hazmi, Nawal E.; Farrag, Ayman A.; Elsayed, Mohamed A.; El-Khawaga, Ahmed M.; El-Sayyad, Gharieb S.; Elshamy, Aliaa A.
Abstract: Magnesium ferrite nanoparticles (Mg Fe2 O4 NPs) was synthesized by a chemical co-precipitation method and characterized via structural and optical properties. The surface of Mg Fe2 O4 NPs was stabilized with citric acid (CA) by a direct addition method (CA-Mg Fe2 O4 NPs), then Amoxicillin (AX) was loaded with CA-Mg Fe2 O4 nanocomposites. Furthermore, their antimicrobial, and antibiofilm activities, growth curve, and effect of UV-illumination methods were examined against different pathogenic microbes. Based on XRD, HRTEM and SEM analyses, it is found that Mg Fe2 O4 NPs are located at the core, while the CA and AX are coated this core. In-vitro zone of inhibition (ZOI) and minimum inhibitory concentration (MIC) results verified that AX-loaded CA-Mg Fe2 O4 nanocomposites exhibited its encouraged antimicrobial activity against S. aureus, E. coli, and C. albicans (32.2, 22.0, and 19.0 mm ZOI, respectively) & (0.312, 0.625, and 1.25 μg/ml MIC, respectively). AX-CA-Mg Fe2 O4 nanocomposites are showed antibiofilm percentage against S. aureus (95.34%), E. coli (93.93%), and C. albicans (76.23%). AX-CA-MgFe2 O4 nanocomposites are an excellent disinfectant agents once they are excited by UV light. Membrane leakage assay explains the formation of holes on the surface of bacteria, and confirms SEM reaction mechanism. AX-loaded CA-Mg Fe2 O4 NPs are promising for potential applications in biomedical uses. Graphical abstract: Image 1 Highlights: Mg Fe2 O4 NPs was synthesized by a chemical co-precipitation method and characterized via structural and optical properties. The surface of Mg Fe2 O4 NPs was stabilized with CA by a direct addition method, then AX has been loaded with CA-Mg Fe2 O4 NPs. Antimicrobial, antibiofilm, growth curve, and UV-illumination effect methods were examined against some pathogenic microbes. AX-CA-MgFe2 O4 NPs is an excellent disinfectant agent once it was excited by UV light. AX-CA-Mg Fe2 O4 NPs are promising for potential applications in biomedical uses.